Morpho-agronomical and biochemical traits screening and genetic variability in selected black cumin (Nigella sativa) mutant lines - El-Mahrouk, Mohammed Elsayed; Maamoun, Mossad Khairy; El-Leel, Omneya Farouk Abu; Dewir, Yaser Hassan; El-Banna, Antar Nasr; Naidoo, Yougasphree; Datta, Subodh Kumar (Penerbit Universiti Kebangsaan Malaysia, 2020)
The production of new Nigella sativa cultivars by plant breeding programs is difficult due to its narrow genetic base. A number of induced morphological traits, yield components and percent content of fatty acid methyl esters in the parent line and nine selected mutants (Mt1-Mt9) have been reported in two generations (M3 and M4) of N. sativa to determine the best genotype to release as a new cultivar. The results showed that Mt2 plants were the tallest (118.3 and 149.7 cm in M3 and M4, respectively). The highest seed yield per plant was measured for Mt5; Mt4 showed the highest per cent of palmitic and stearic acids, 11.93% and 13.70%, respectively; whereas Mt8 had the highest percent content (45.67%) of linoleic acid. Five Inter Simple Sequence Repeat (ISSR) markers were used to investigate genetic variability within mutant lines and their parent. These primers generated 71 reproducible and scorable amplification products across the genotypes tested. Fifty-eight of these fragments were highly polymorphic (81.7%). The proportion of common bands (13) was low (18.3%). All primers produced unique fragments and generated 33 specific alleles. The average number of amplification products per primer was 14.2. The size of ISSR amplified fragments varied from 1109 to 148 base pairs (bp). The similarity between each mutant and the parent line varied from 0.56% to 100%. Finally, the present investigation indicated that mutants Mt5 and Mt6 are promising high yielding genotypes which can be recommended as new cultivars, whereas Mt3 and Mt7 possess an attractive phenotype appropriate for ornamental use.